COMPREHENSIVE MODEL‐BASED ENGINEERING FOR SYSTEMS OF SYSTEMS. Issue 3 (21st November 2016) - John, Fitzgerald
ABSTRACT: Systems of systems (SoS) place particular demands on model‐based engineering, arising from the uncertainty inherent in dealing with independent constituent systems, the need to obtain confidence in the end‐to‐end capabilities of the SoS, and the challenges of integrating diverse domain‐specific terminologies, models, and tools. This paper describes the approach taken by the COMPASS project in developing and validating model‐based methods for SoS engineering (SoSE). Architectural frameworks, profiles and modelling patterns implement a contractual approach that deals with uncertainty by allowing abstract specification of the assumptions and guarantees between SoS constituents. These are underpinned by a formal semantic framework that permits the verification of SoS‐level properties arising from the composition of diverse constituent system contracts. The whole approach has been realized in an open tools framework and validated through applications in home audio/video networks and in emergency response service reengineering. The paper outlines and exemplifies the technologies developed within COMPASS and looks forward to the emerging challenges of cyber‐physical SoS.